INDIKASI GEOGRAFIS UNTUK PENINGKATAN PASAR WAYANG PURBA SRAGEN: ANALISIS INSTITUSIONAL - Farid Adi Prasetya; Sidiq Permono Nugroho; Fery Indra Kurniawan (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
This research proposes a market recognition enhancement of wayang purba, a traditional indigenous performance from Ngebung Village, Sragen Regency, through Geographical Indications (GIs) registration. The research applies qualitative methods to explore the roles of academia, business, government, community, and media using the Institutional Analysis Development (IAD) framework by Elinor Ostrom. The IAD framework delivers the authentic potential of Sragen as a prehistoric site and a part of Central Java with solid roots in wayang performances. On the contrary, the analysis also found that stakeholder support still needed to run partially, overlapping roles that failed to achieve collective efforts in carrying Wayang Purba to gain recognition of GIs. The importance of GIs in increasing market recognition of indigenous art products underlies research suggestions on managing the roles of stakeholders in a more integrated manner. Research recommendations align with previous literature that the GIs scheme is the right step for cultural marketing that needs to be managed collectively. Even so, an in-depth exploration of the duties and functions of each institution still needs to be implemented in future research.